FEATURES OF DIAGNOSTIC AND THERAPEUTIC TACTICS FOR BLUNT ABDOMINAL TRAUMA WITH DAMAGE TO THE PANCREAS - A. B. Singayevsky; S. G. Scherbak; B. V. Sigua; N. M. Vrublevsky; A. V. Nikiforenko; A. A. Kurkov; A. K. Dyukov (Неотложная медицинская помощь)
Abstract. Injuries of pancreas in the closed abdominal trauma remain the one of most challenging issues in diagnosis and choice of optimal therapy.Objectives. To analyze clinical results of the improved diagnostic and treatment tactics in patients with blunt abdominal trauma and damage to the pancreas.Material and methods. We report the results of treatment for 141 patients with pancreatic trauma treated from 1991 to 2015 at City Hospital No. 3 and City Hospital No. 40. All patients were divided into 2 groups. These groups were formed according to the time factor. The groups were comparable in age, gender, and pancreatic trauma severity. The study group consisted of 59 patients, treated in 2004-2015, and the comparison group consisted of 82 patients (1991–2003). The advanced diagnostic and treatment algorithm for the study group included modern instrumental diagnostic methods, such as ultrasound, computed tomography, diagnostic laparoscopy and improved surgical tactics to lower indications for omental plug, omentobursostomy, suturing capsule of pancreas and cholecystostomy.Results. This algorithm reduced the duration gap between hospitalization and surgery averagely from 10.7 to 4.0 hours, and the modified treatment tactics decreased the incidence of septic complications from 15.8% to 6.8%, and the mortality from 27.6% to 16.9%.Conclusion. As a rule, methods of radiodiagnosis detect only indirect signs of pancreatic injury in blunt abdominal trauma. It is advisable to perform omental plugging only as medical tactics of «damage control».